Global geomorphology : an introduction to the study of landforms - Summerfield, M. A (Michael A) (Pearson Education, 1991)
The plate tectonics revolution in the earth sciences has provided a valuable new framework for understanding long-term landform development. This innovative text provides a comprehensive introduction to the subject of global geomorphology, with the emphasis placed on large-scale processes and phenomena. Integrating global tectonics into the study of landforms and incorporating planetary geomorphology as a major component the author discusses the impact of climatic change and the role of catastrophic events on landform genesis and includes a comprehensive study of surface geomorphic processes.